2012
DOI: 10.1103/physrevlett.108.237602
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission of Electrons Generated by the Near Field of Strongly Coupled Plasmons

Abstract: Field emission of electrons is generated solely by the ultrastrong near-field of strongly coupled plasmons without the help of a noticeable dc field. Strongly coupled plasmons are excited at Au nanoparticles in subnanometer distance to a Au film by femtosecond laser pulses. Field-emitted electrons from individual nanoparticles are detected by means of photoelectron emission microscopy and spectroscopy. The dependence of total electron yield and kinetic energy on the laser power proves that field emission is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 29 publications
5
64
1
1
Order By: Relevance
“…Regarding the mechanism of the nonlinear photoemission, it is also worth noting that field emission is possible as argued in a recent report. 45 The field emission occurs at the lowfrequency/high-intensity limit of the electric field induced by the electron ejection and is thus referred to as a tunneling emission. The laser intensity used in this study was typically on the order of 10 MW cm 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the mechanism of the nonlinear photoemission, it is also worth noting that field emission is possible as argued in a recent report. 45 The field emission occurs at the lowfrequency/high-intensity limit of the electric field induced by the electron ejection and is thus referred to as a tunneling emission. The laser intensity used in this study was typically on the order of 10 MW cm 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the data yields peak values up to 45 μA. Combined with an effective cross-section of ∼80 nm 2 (Fig. 3b,c), we obtain sub-cycle current densities exceeding 50 MA cm -2 , driven at room temperature and without damaging the device.…”
mentioning
confidence: 88%
“…The high peak electric fields provided by single-cycle light pulses can be harnessed to manipulate and control charge motion in solid-state systems, resulting in electron emission out of metals and semiconductors [1][2][3][4][5][6] or high harmonics generation in dielectrics 7,8 . These processes are of a non-perturbative character and require precise reproducibility of the electric-field profile [9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…In the experiments reported in this paper, we estimate the peak intensity incident on the sample to be on the order of 5*10 9 W/cm 2 . Compared to previous PEEM studies using 800 nm light, this intensity is in the high part of the reported ranges [11][12][13], which is expected due to the lower photon energy. The laser beam is s-polarized, i.e.…”
Section: Methodsmentioning
confidence: 81%
“…This further implies that the intensities required for imaging are likely to be beyond the perturbative regime of direct n-photon photoemission via virtual states. Other mechanisms such as field emission [13], thermal emission [24], and defect-mediated emission [25], as well as combinations of the above [26], have been proposed to generate electron emission by optical pulses. Regardless of the exact mechanism involved, the laser-induced emission of an electron from Ag will due to energy conservation require at least six 0.8 eV photons, and the photoelectron yield is expected to depend non-linearly on the local near-field intensity.…”
mentioning
confidence: 99%